Bacterial peptidoglycan levels have brain area, time of day, and sleep loss-induced fluctuations - English, Erika L.; Krueger, James M. (Frontiers in Neuroscience, 2025)
Sleep-inducing bacterial cell wall components isolated from brain and urine of sleep deprived animals were identified as peptidoglycan (PG) and muropeptides in the 1980s. Following host detection of PG/muropeptides, downstream signaling mechanisms include release of effector molecules, e.g., cytokines involved in sleep regulation. Understanding of physiological brain PG changes has remained limited, in part due to the historic difficulties of PG quantitation. Herein, we report murine brain PG levels in multiple brain areas within the context of animals’ rest-wake cycles and after sleep loss. Significant time-of-day changes in brain PG levels occurred in all brain areas; lowest levels occurred during the transition from rest to wake periods, at zeitgeber time 12 (ZT12). Highest levels of PG were in brainstem while olfactory bulb, hypothalamic, and cortical PG levels were lower. After 3 h of sleep disruption, PG levels increased in the somatosensory cortex, but decreased in brainstem, and hypothalamus. After 6 h of sleep disruption, PG increased in the brainstem and olfactory bulb compared to control levels. Further, RNA-seq analyses of somatosensory cortical tissue was used to assess sleep loss-dependent changes in genes previously linked to PG. Multiple PG-related genes had altered expression with sleep loss including PG binding and signaling molecules, e.g., Pglyrp1 and Nfil3. In summary, brain PG levels were dependent on time of day, brain area, and sleep history. Further, sleep loss altered brain gene expression for PG-linked genes. Collectively, these data are consistent with the hypothesis that microbe-host symbiotic interactions are involved in murine sleep regulatory mechanisms.